PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK GEDUNG RUSUNAWA YAYASAN ALMUSLIM KABUPATEN BIREUEN - Sakura, Royanna; Putra, Reza; Masrura, Delfian; Sazali, Munawir (Malikussaleh Journal of Mechanical Science and Technology, 2023)
Employment agency such as construction companies must maintain and provide the health of employees, this health comprehensively includes the physical and mental health of workers. Poor worker health can have unfavorable effects for both the worker and the company. Occupational health programs can be carried out by creating a healthy work environment. In the implementation, the occupational health program is always followed by an occupational safety program because the two programs are interrelated in the maintenance of workers. Occupational safety is safety related to the use of the latest technology such as machines, work equipments, materials and processing, the foundation of the place and the environment and steps of the work. Occupational safety and health can help make workers feel comfortable, safe and secure in carrying out the obligations to the company. The purpose of this research was to determine the application of Occupational Safety and Health (OSH) and the comfort level of workers at PT. Wandra Cipta Engineering Consultant in the tenement (Rusunawa) building project of the Almuslim foundation, Bireuen Regency. The research method used in this research was a quantitative method including surveys, questionnaires and interviews while data processing was done by using SPSS software version 25. The results of the research indicated that Occupational Safety and Health (OSH) and the comfort level of workers at PT. Wandra Cipta Engineering Consultant in the tenement (Rusunawa) building project of the Almuslim foundation, Bireuen Regency was very comfortable. This can be seen from the results of data processing on occupational safety and health, it was found that 58.57% of the respondents agreed and the reliability test was 0.724 and 0.843. respectively